Symposium 9: Networked Learning and Networked Information: Towards a Theoretical Basis for the Development of Integrated Information Environments - Brophy, Peter (Proceedings of the International Conference on Networked Learning, 2004)
In recent years it has become clear that networked information environments need to be closely integrated with the environments in which their users undertake their mainstream tasks and activities. The EDNER project, undertaking a formative evaluation of a major national information environment, provided an opportunity to explore the ways in which information resources were being integrated into learning and teaching within the United Kingdom. In this paper the Director of the EDNER project describes the work that has been carried out and summarises some of the key findings. The paper suggests that integration between different environments, including those delivering information and those supporting learning, is the key requirement. As we move towards ever more complex networked environments, including those driven by complex interactions between “objects” of many different kinds, it will be necessary to revisit the underlying theories and paradigms which have been developed by researchers and practitioners operating within their own areas of expertise.